1979
DOI: 10.1139/y79-061
|View full text |Cite
|
Sign up to set email alerts
|

The effects of muscarinic receptor blockers on the turnover rate of acetylcholine in various regions of the rat brain

Abstract: The actions of antimuscarinic agents (benztropine, trihexyphenidyl, and scopolamine) on the dynamics of acetylcholine (ACh) in central cholinergic neurons were examined in various rat brain areas. It was found that the pattern of changes in ACh turnover (TRACh) elicited by these drugs exhibited marked regional variations. After administration of the anticholinergic drugs, the TRACh in hippocampus and thalamus was increased, in cortex it was decreased, and in striatum it was unchanged. ACh concentration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…He suggested that this could arise from previously described APOE4 isoform-specific reductions in the transport of cholesterol and phospholipids, such as phosphatidylcholine and phosphatidylethanolamine, which can serve as precursors to choline in the synthesis of acetylcholine. In animal experiments, the administration of an antimuscarinic challenge, such as the one employed in the current experiment, has been shown to be accompanied by compensatory increases in acetycholine release in various brain regions including the hippocampus (Michikawa et al, 2000;Wood and Cheney, 1979). Thus, reductions in Ach synthetic capacity associated with the e4 allele, if confirmed, may reduce the efficiency of the central cholinergic system in overcoming a muscarinic blockade and thereby contribute to our observations.…”
Section: Discussionsupporting
confidence: 52%
“…He suggested that this could arise from previously described APOE4 isoform-specific reductions in the transport of cholesterol and phospholipids, such as phosphatidylcholine and phosphatidylethanolamine, which can serve as precursors to choline in the synthesis of acetylcholine. In animal experiments, the administration of an antimuscarinic challenge, such as the one employed in the current experiment, has been shown to be accompanied by compensatory increases in acetycholine release in various brain regions including the hippocampus (Michikawa et al, 2000;Wood and Cheney, 1979). Thus, reductions in Ach synthetic capacity associated with the e4 allele, if confirmed, may reduce the efficiency of the central cholinergic system in overcoming a muscarinic blockade and thereby contribute to our observations.…”
Section: Discussionsupporting
confidence: 52%
“…The parietal cortex and hippocampus were subsequently processed for the gas chromatography-mass fragmentographic assay of ACh and Ch and the incorporated deuterium Wood and Peloquin, 19821. The acetylcholine turnover (TRACJ was calculated for each animal using single time point analysis as described previously m o o d and Cheney, 1979;.…”
Section: Acetylcholine Turnovermentioning
confidence: 99%
“…§1734 solely to indicate this fact. Endogenous and deuterated choline and AcCho content of various brain regions were analyzed by gas chromatography/ mass spectrometry (7). From the percentage of incorporation of the deuterated precursor into choline and AcCho, the fractional rate constant for AcCho efflux was determined.…”
Section: Methodsmentioning
confidence: 99%